2023
DOI: 10.1192/bjo.2023.28
|View full text |Cite
|
Sign up to set email alerts
|

Benefits following community treatment orders have an inverse relationship with rates of use: meta-analysis and meta-regression

Abstract: Background Community treatment order (CTO) use in Australia and New Zealand ranges from less than 40 per 100 000 population in Western Australia and Canterbury to over 100 per 100 000 in Victoria, South Australia and Waitemata. Recent publications on CTO use now permit a meta-regression to investigate whether differences in CTO use by jurisdiction affect either the possible predictors or outcomes of CTOs. Aims To assess whether factors associated with CTO placement or subsequent outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…There is evidence that clinicians adapt to changing legislation and patients with the most severe illnesses (associated with risks or lack of capacity) continue to be treated compulsorily despite legislative change. 14 However, we also believe that recent research, such as Kisely et al's excellent analysis, 10 is assisting the field by informing which outcomes different patient groups are likely to experience on CTOs and that this will improve care for patients and families.…”
Section: Uniformity Of Use Legislative Change and Alternatives To Ctosmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that clinicians adapt to changing legislation and patients with the most severe illnesses (associated with risks or lack of capacity) continue to be treated compulsorily despite legislative change. 14 However, we also believe that recent research, such as Kisely et al's excellent analysis, 10 is assisting the field by informing which outcomes different patient groups are likely to experience on CTOs and that this will improve care for patients and families.…”
Section: Uniformity Of Use Legislative Change and Alternatives To Ctosmentioning
confidence: 99%
“…Benefits following community treatment orders have an inverse relationship with rates of use: a meta-analysis and meta-regression by Kisely et al in a recent issue of the BJPsych Open is important because it provides clues on which patient groups may benefit from compulsory treatment. 10 CTO use in Australasia was examined to evaluate whether factors associated with CTO use or subsequent outcomes vary according to rates of use. Kisely et al confirm the well-established finding that CTO use varies substantially between regions.…”
Section: The Evidence Basementioning
confidence: 99%
“…The negative effects of restrictive practices are not just confined to the hospital setting. A meta-analysis and meta-regression of community treatment order (CTO) usage conducted by Kisely et al (2023) found there is no evidence that CTOs reduce bed-days or admissions or that they address the issue of the 'revolving door'. Moreover, the review found that people from a migrant background were 47% more likely to be subjected to CTOs.…”
Section: A I Nst R Ea M P Syc H I At Ry I S R a Pi Dly Ru N N I Ng Ou...mentioning
confidence: 99%